Pengaruh Tingkat Pendidikan dan Upah Minimum terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan Tahun 2014 – 2018 - Alamsyah; Muhammad Effendi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This Research was conducted to (1) Determine the influence of education leveland minimum wages on labor absorption in 13 districts/cities in South KalimantanProvince; (2) Determine the most dominant factor in influencing labor absorption inthe Province of South Kalimantan.This Research is included in the type of quantitative descriptive Research.While the location of this study is 13 districts / cities in South Kalimantan Province,and the object of this study is the data of education level and minimum wage in SouthKalimantan during 2014 - 2018. The data obtained is then processed using panel dataregression analysis with fixed-effect models using the EVIEWS 10 program.The results of this Research indicate that (1) The level of education andminimum wages simultaneously have a significant effect on labor absorption in theProvince of South Kalimantan in 2014 - 2018; (2) The results of this study alsoindicate that the level of education is the most dominant factor affecting laborabsorption in South Kalimantan in 2014 – 2018